A study on the effect of grommet as partial ossicular replacement prosthesis in type III tympanoplasty in patients with chronic suppurative otitis media - Prakash, M. D.; Joy, Lyra; Jose, Priya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic otitis media (COM) with or without cholesteatoma causes ossicular erosion/ destruction which leads to conductive hearing loss. Ossiculoplasty is to reconstruct the hearing mechanism in ear after eliminating the disease from the middle ear. In our study we used ventilation tubes or grommet as partial ossicular replacement prosthesis (PORP) for the reconstruction of the ossicular chain especially when the stapes is mobile. The objective of the study is to assess the degree of hearing improvement by using grommet as PORP in type III tympanoplasty. Methods: It was an observational study from July 2018 to July 2019. 20 patients with COM undergoing canal wall up or canal wall down mastoidectomy with intraoperative ossicular chain erosion with intact stapes suprastructure were included in this study. Post-operative hearing gain and graft uptake was assessed at 3rd month. Results: Among these 20 patients 15 underwent canal wall up mastoidectomy with type III tympanoplasty and 5 underwent canal wall down procedure with type III tympanoplasty. Incus was eroded in 17 cases, malleus in 2 cases and malleus with incus eroded in 1 case. The pre op average airborne gap was 38 dB and mean improvement of 12 dB was observed at third month. Conclusions: Grommet tube used as PORP is an effective alternative in the reconstruction of ossicular chain with good hearing improvement.